The Contribution of Circular Tourism to the Sustainable Development of Greece - Economou, Agisilaos (Archives of Business Research, 2022)
Tourism today is an organized activity, which serves a variety of travelers’ entertainment needs, but at the same time brings financial resources to the places that receive visitors. In other words, it is an economic activity that lies in the laws of supply and demand. Therefore, the process of tourism development is largely related to what a place has to offer in terms of natural and cultural resources and services, and is a positive economic process which brings financial resources to the place that develops it. However, in many Greek tourist destinations, due to the increased number of tourists they receive, there is an over-consumption of their resources and an imbalance in relation to the carrying capacity of the area. As a solution to the environmental and social problems created by tourism, in the present work, circular tourism is proposed for Greece. That is, the one who is based on the respect and preservation of socio-cultural and environmental resources, as well as the harmonious coexistence of tourists-visitors and employees in the tourism sector and the local community